ANALISIS BIAYA OPERASIONAL DALAM MENINGKATKAN KINERJA KEUANGAN PADA PT. PEGADAIAN (PERSERO) TBK - Alifia Dilaini Amril; Ruzikna " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study aims to determine the development and analyze operational costs in improving financial performance at PT. Pegadaian (Persero) Tbk during the 2016-2020 period. The subjects in this study were PT. Pegadaian (Persero) Tbk and research object: Financial statements for the period 2016-2020 which include items in the balance sheet and income statement. The data collection method used in this research is documentation. Data and information obtained from the website of PT. Pegadaian (Persero) Tbk. The data analysis method used in this study is the Analysis of Operating Cost Ratios and Financial Ratios. From the results of data analysis research (1) Operational Cost Analysis with indicators of the Ratio of Operating Costs to Operating Income, the Marketing Cost Ratio and General Administration Expenses Ratio in a healthy condition. (2) Profitability Ratio Analysis with indicators of Net Profit Margin (NPM), and Gross Profit Margin in good condition, while Return On Assets (ROA) and Return On Investment (ROI) are not in good condition.Keywords: Operational Costs, Marketing Costs, General Administration Costs, and  Profitability.